(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to identify the impact of mobile banking technology on the dimensions of the quality of banking services in the studied banks, in addition to explaining the significant differences in the answers of the researched sample regarding to the two research variables (mobile banks technology, the dimensions of the quality of banking services) and according to the personal variables, The research problem was defined by the main question which is: (What is the impact of mobile banks technology on the dimensions of the quality of the banking services?). The research was applied in a sample of Iraqi banks which was (International Development Bank, Baghdad Bank, National Bank of Iraq, Trade Bank of Iraq, Taif Islamic Bank, Iraqi Islamic Bank, and International Islamic Bank), The research relied on the descriptive analytical approach in dealing with the subject and employing a questionnaire to collect data from a sample of (371) customers of the studied banks and using the statistical program (SPSS V.26) to reach the results. The research reached to many of results the most important of it are the following: • There is agreement on the importance of the mobile bank and its impact in simplifying the procedures for obtaining banking services with high efficiency away from routine transactions. It also provides a high level of privacy and security in performing banking operations. • The researched banks need to support their mobile banking application, and listening to customer recommendations for the purpose of developing it, making it easier to use, and including a more of services to satisfy customers.